Association between blood pressure variability, cardiovascular disease and mortality in type 2 diabetes: A systematic review and meta‐analysis. Issue 12 (9th August 2019) - Chiriacò, Martina; Pateras, Konstantinos; Virdis, Agostino; Charakida, Marietta; Kyriakopoulou, Despoina; Nannipieri, Monica; Emdin, Michele; Tsioufis, Konstantinos; Taddei, Stefano; Masi, Stefano; Georgiopoulos, Georgios
Abstract: Aim: To investigate the associations of blood pressure variability (BPV), expressed as long‐term (visit‐to‐visit) and short‐term (ambulatory blood pressure monitoring [ABPM] and home blood pressure monitoring [HBPM]) and all‐cause mortality, major adverse cardiovascular events (MACEs), extended MACEs, microvascular complications (MiCs) and hypertension‐mediated organ damage (HMOD) in adult patients with type 2 diabetes. Materials and methods: PubMed, Medline, Embase, Cinahl, Web of Science, ClinicalTrials.gov and grey literature databases were searched for studies including patients with type 2 diabetes, at least one variable of BPV (visit‐to‐visit, HBPM, ABPM) and evaluation of the incidence of at least one of the following outcomes: all‐cause mortality, MACEs, extended MACEs and/or MiCs and/or HMOD. The extracted information was analyzed using random effects meta‐analysis and meta‐regression. Results: Data from a total of 377 305 patients were analyzed. Systolic blood pressure (SBP) variability was associated with a significantly increased risk of all‐cause mortality (HR 1.12, 95% CI 1.04–1.21), MACEs (HR 1.01, 95% CI 1.04–1.17), extended MACEs (HR 1.07, 95% CI 1.03–1.11) and MiCs (HR 1. 12, 95% CI 1.01–1.24), while diastolic blood pressure was not. Associations were mainly driven from studies on long‐term SBP variability. Qualitative analysis showed that BPV was associated with the presence of HMOD expressed as carotid intima‐media thickness, pulse wave velocity and left ventricular hypertrophy. Results were independent of mean blood pressure, glycaemic control and serum creatinine levels. Conclusions: Our results suggest that BPV might provide additional information rather than mean blood pressure on the risk of cardiovascular disease in patients with type 2 diabetes.